Elast PQ Ultrasound - a Noninvasive, Reproducible, Easily Performed Method and a New Era in Liver Fibrosis Assessment (Faridpur Medical College Journal, 2018)
Liver fibrosis represents the repair mechanism in liver injury and is a feature of most chronic liver diseases. The degree of liver fibrosis in chronic viral hepatitis infection has major clinical implications and presence of advanced fibrosis or cirrhosis determines prognosis. Treatment initiation for viral hepatitis is indicated in most cases of advanced liver fibrosis and diagnosis of cirrhosis entails hepatology evaluation for specialized clinical care. Liver biopsy is an invasive technique and has been the standard of care of fibrosis assessment for years; however, it has several limitations and procedure related complications. Recently, several methods of noninvasive assessment of liver fibrosis have been developed which require either serologic testing or imaging of liver. Imaging based noninvasive techniques are reviewed here and their clinical use is described. Some of the imaging based tests are becoming widely available, and collectively they are shown to be superior to liver biopsy in important aspects. Clinical utilization of these methods requires understanding of performance and quality related parameters which can affect the results and provide wrong assessment of the extent of liver fibrosis. Familiarity with the strengths and weakness of each modality is needed to correctly interpret the results in appropriate clinical content. A new technique called Elast PQ uses ultrasound shear wave elastography to provide a noninvasive, reproducible, easily performed method of assessing liver fibrosis. It can easily combine a routine ultrasound imaging exam of the liver anatomy with targeted tissue stiffness values, assess liver fibrosis in patient with clinically suspected disease even before abnormalities are detected with ultrasound imaging, evaluate and obtain a baseline stiffness value in patients with chronic liver disease, follow up patients under treatment to monitor progression, stabilization or regression of liver disease and help avoid the need for liver biopsies when elastography results are consistent with other clinical findings. Both the prognosis and potential treatment of chronic liver diseases greatly depend on the progression of liver fibrosis, which is the ultimate outcome of chronic liver damage. Historically, liver biopsy has been instrumental in adequately assessing patients allows clinicians both to obtain diagnosis information and initiate adequate therapy. However, the technique is not exempt of deleterious effects. Multiple diagnostic tests have been developed for the staging of fibrosis using noninvasive methods, most of them in the setting of chronic hepatitis C. The goal of this paper is to review available data on the staging and assessment of liver fibrosis with two methods: serum markers & transient elastography (FibroScan).Faridpur Med. Coll. J. Jan 2018;13(1): 44-46